Analysis of Financial Statements Based on Liquidity, Profitability, and Solvency Ratios in Small and Medium Enterprises: A Case Study of SME Siska Wijaya Beauty Salon in Dau District, Malang Regency - Fransiska Yolin Sunardi; Cakti Indra Gunawan; Noviana Yaniar Suprajitno (International Research & Development for Human Beings (IRDH), 2026)
This study aims to evaluate the financial condition of Siska Wijaya Beauty Salon, a small and medium-sized enterprise (SME) located in Dau District, Malang Regency, using a financial ratio analysis approach encompassing the dimensions of liquidity, profitability, and solvency over a three-year period (2023–2025). A qualitative descriptive approach was employed, utilizing primary data from balance sheets and income statements obtained through documentation and in-depth interviews with the business owner and treasurer. The findings indicate that the liquidity condition of the enterprise is healthy, as evidenced by Current Ratio and Quick Ratio values exceeding the acceptable threshold. In terms of profitability, the values of Return on Assets (ROA), Net Profit Margin (NPM), and Return on Equity (ROE) exhibited fluctuations but were generally categorized as good to excellent. Regarding solvency, the Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), and Debt to Capital Ratio (DCR) confirmed that the majority of the business financing originated from owner's equity, with debt proportions remaining controlled at below 50%. The research affirms that, despite the simplicity of the financial recording system currently in place, the SME has demonstrated an ability to sustain financial stability and manage resources efficiently. The managerial implication of this study underscores the importance of formalizing the financial recording system in accordance with EMKM accounting standards to strengthen the foundation for business decision-making.